APPLICATION OF JAKARTA FLOATING FARM AND FISHERIES (J3F) CONCEPT AS FUTURE URBAN-COASTAL LIVEHOOD SOLUTION - Prayoga, Danang; Trianto, Wawan; Haru, Hamzah; Lopes, Daniel Jeremias; Puspita, Indah (Program Kreativitas Mahasiswa - Gagasan Tertulis, 2014)
Jakarta is the central part of governance, economic, and industrial aspect of Indonesia. This condition make Jakarta as the most populated metropolitan. DKI Jakarta covers an area 650 km2 wide and have population density around 12.495 people/km2. The population grow around 2.4 % per year. A fast-growing population and environmental capacity decrease causing high food demand and open land scarcity. Jakarta have an area 66.233 Ha with agriculture area around 1.102 Ha and non-agriculture area 65.131 Ha. Most food supply comes from Bogor, Bekasi and Tangerang which are three satellite cities of Jakarta. In consequence, a solution is urgently needed to overcome the whole problems. Jakarta Floating Farm and Fisheries (J3F) is the floating agricultural farm and floating fisheries. This concept is new alternative for agriculture and fisheries development utilzing coastal zone and act as an effort for creating a new leading, modern and eco-friendly agricultural and fisheries industry supporting an independent metropolitan concept. Jakarta Floating Farm and Fisheries (J3F) concept will directly integrate with Jakarta North coastal area development masterplan in form of Garuda giant seawall as a government program facing Jakarta north coastal zone protection from sinking. Various attempt in synergy with nature are applicated at most of the metropolitan system so that more marine and nature damage could be avoided.Keyword: Residence, Farming, Fisheries, Jakarta